Disaster Risk Management in an Age of Climate Change: A Summary of the April 3, 2008 Workshop of the Disasters Roundtable - National Research Council (The National Academies Press, 2009)
Keywords: Behavioral and Social Sciences; Environment and Environmental Studies; Conflict and Security Issues

A Data Foundation For The National Spatial Data Infrastructure (The National Academies Press, 1995)
Keywords: Earth Sciences

Geological and Geotechnical Engineering in the New Millennium: Opportunities for Research and Technological Innovation - National Research Council (The National Academies Press, 2006)
The field of geoengineering is at a crossroads where the path to high-tech solutions meets the path to expanding applications of geotechnology. In this report, the term "geoengineering" includes all types of engineering that deal with Earth materials, such as geotechnical engineering, geological engineering, hydrological engineering, and Earth-related parts of petroleum engineering and mining engineering. The rapid expansion of nanotechnology, biotechnology, and information technology begs the question of how these new approaches might come to play in developing better solutions for geotechnological problems.
Keywords: Earth Sciences; Engineering and Technology

Possible Health Effects of Exposure to Residential Electric and Magnetic Fields - National Research Council (The National Academies Press, 1997)
Can the electric and magnetic fields (EMF) to which people are routinely exposed cause health effects? This volume assesses the data and draws conclusions about the consequences of human exposure to EMF. The committee examines what is known about three kinds of health effects associated with EMF: cancer, primarily childhood leukemia; reproduction and development; and neurobiological effects. This book provides a detailed discussion of hazard identification, dose-response assessment, exposure assessment, and risk characterization for each. Possible Health Effects of Exposure to Residential Electric and Magnetic Fields also discusses the tools available to measure exposure, common types of exposures, and what is known about the effects of exposure. The committee looks at correlations between EMF exposure and carcinogenesis, mutagenesis, neurobehavioral effects, reproductive and developmental effects, effects on melatonin and other neurochemicals, and effects on bone healing and stimulated cell growth.
Keywords: Environment and Environmental Studies; Math, Chemistry, and Physics

Improving Health in the United States: The Role of Health Impact Assessment - National Research Council (The National Academies Press, 2011)
Factoring health and related costs into decision making is essential to confronting the nation's health problems and enhancing public well-being. Some policies and programs historically not recognized as relating to health are believed or known to have important health consequences. For example, public health has been linked to an array of policies that determine the quality and location of housing, availability of public transportation, land use and street connectivity, agricultural practices and the availability of various types of food, and development and location of businesses and industry. Improving Health in the United States: The Role of Health Impact Assessment offers guidance to officials in the public and private sectors on conducting HIAs to evaluate public health consequences of proposed decisions—such as those to build a major roadway, plan a city's growth, or develop national agricultural policies—and suggests actions that could minimize adverse health impacts and optimize beneficial ones. Several approaches could be used to incorporate aspects of health into decision making, but HIA holds particular promise because of its applicability to a broad array of programs, consideration of both adverse and beneficial health effects, ability to consider and incorporate various types of evidence, and engagement of communities and stakeholders in a deliberative process. The report notes that HIA should not be assumed to be the best approach to every health policy question but rather should be seen as part of a spectrum of public health and policy-oriented approaches. The report presents a six-step framework for conducting HIA of proposed policies, programs, plans, and projects at federal, state, tribal, and local levels, including within the private sector. In addition, the report identifies several challenges to the successful use of HIA, such as balancing the need to provide timely information with the realities of varying data quality, producing quantitative estimates of health effects, and engaging stakeholders.
Keywords: Environment and Environmental Studies; Health and Medicine

Urban Meteorology: Forecasting, Monitoring, and Meeting Users' Needs - National Research Council (The National Academies Press, 2012)
According to the United Nations, three out of five people will be living in cities worldwide by the year 2030. The United States continues to experience urbanization with its vast urban corridors on the east and west coasts. Although urban weather is driven by large synoptic and meso-scale features, weather events unique to the urban environment arise from the characteristics of the typical urban setting, such as large areas covered by buildings of a variety of heights; paved streets and parking areas; means to supply electricity, natural gas, water, and raw materials; and generation of waste heat and materials.
Keywords: Earth Sciences; Environment and Environmental Studies

Coal: Research and Development to Support National Energy Policy - National Research Council (The National Academies Press, 2007)
Coal will continue to provide a major portion of energy requirements in the United States for at least the next several decades. It is imperative that accurate information describing the amount, location, and quality of the coal resources and reserves be available to fulfill energy needs. It is also important that the United States extract its coal resources efficiently, safely, and in an environmentally responsible manner. A renewed focus on federal support for coal-related research, coordinated across agencies and with the active participation of the states and industrial sector, is a critical element for each of these requirements.
Keywords: Energy and Energy Conservation; Industry and Labor

Research Priorities for Airborne Particulate Matter: I. Immediate Priorities and a Long-Range Research Portfolio - National Research Council (The National Academies Press, 1998)
New National Ambient Air Quality Standards for airborne particles smaller than 2.5 micrometers, called PM2.5, were issued by the U.S. Environmental Protection Agency (EPA) amidst scientific uncertainty and controversy. In response to a request from Congress, Research Priorities for Airborne Particulate Matter, the first of four books in a series, offers a conceptual framework for an integrated national program of particulate-matter research, identifies the 10 most critical research needs linked to key policy-related scientific uncertainties, and describes the recommended timing and estimated costs of such research. The committee concludes that EPA should devote more resources to investigating the relationships between fixed-site outdoor monitoring data and actual human breathing-zone exposures to ambient particulate matter and to identifying the most biologically important constituents and characteristics of particulate matter through toxicological studies. The recommended research activities are critical to determining actual exposures of human subpopulations most susceptible to harm from the most hazardous constituents of particulate matter. Future research will be an investment in public health and a means to ensure that resources spent on control technology and regulatory compliance will have a reasonable probability of success.
Keywords: Environment and Environmental Studies

The Emergency Manager of the Future: Summary of a Workshop - National Research Council (The National Academies Press, 2003)
From hurricanes to terrorism; natural, technological, and other disasters can have potentially life-threatening effects. Emergency managers of the future will need to have the necessary skills to be prepared for these and other events. The workshop discusses the role and responsibility of emergency managers of the future and the resources needed to meet forthcoming challenges.
Keywords: Earth Sciences

Understanding the Changing Planet: Strategic Directions for the Geographical Sciences - National Research Council (The National Academies Press, 2010)
From the oceans to continental heartlands, human activities have altered the physical characteristics of Earth's surface. With Earth's population projected to peak at 8 to 12 billion people by 2050 and the additional stress of climate change, it is more important than ever to understand how and where these changes are happening. Innovation in the geographical sciences has the potential to advance knowledge of place-based environmental change, sustainability, and the impacts of a rapidly changing economy and society.
Keywords: Earth Sciences; Education

Adaptive Management for Water Resources Project Planning - National Research Council (The National Academies Press, 2004)
This book reviews the Corps of Engineers' experiences to date with the concept of “adaptive management” and provides advice on additional and more effective implementation of this planning approach. The adaptive management concept itself is complex and evolving, but might be summarized as “learning while doing.” The book reviews literature on adaptive management and notes that a range of adaptive management practices present themselves for Corps projects. It is noted that there is no “cookbook” approach to adaptive management, and the book encourages the Corps of Engineers to continue to work with and learn from its applications of the concept. To facilitate institutional learning and to ensure that experiences are being employed across the agency, the book recommends that a Corps Center for Adaptive Management be established. The book also notes that greater involvement from the administration and Congress will be essential to successful adaptive management applications, as the Corps' efforts in this area will benefit from clarified water resources management objectives, the authority to manage adaptively, and from resources necessary for programs such as stakeholder collaboration and post-construction evaluations.
Keywords: Earth Sciences

Review of New York State Low-Level Radioactive Waste Siting Process - National Research Council (The National Academies Press, 1996)
This book reviews the efforts of New York state to site a low-level radioactive waste disposal facility. It evaluates the nature, sources, and quality of the data, analyses, and procedures used by the New York State Siting Commission in its decisionmaking process, which identified five potential sites for low-level waste disposal. Finally, the committee offers a chapter highlighting the lessons in siting low-level radioactive waste facilities that can be learned from New York State's experience.
Keywords: Environment and Environmental Studies

Ozone-Forming Potential of Reformulated Gasoline - National Research Council (The National Academies Press, 1999)
The Committee on Ozone-Forming Potential for Reformulated Gasoline was asked whether the existing body of scientific and technical information is sufficient to permit a robust evaluation and comparison of the emissions from motor vehicles using different reformulated gasolines based on their ozone-forming potentials and to assess the concomitant impact of that approach on air-quality benefits of the use of oxygenates within the RFG program. As part of its charge, the committee was asked to consider (1) the technical soundness of various approaches for evaluating and comparing the relative ozone-forming potentials of RFG blends, (2) technical aspects of various air-quality issues related to RFG assessment, and (3) the sensitivity of evaluations of the relative ozone-forming potentials to factors related to fuel properties and the variability of vehicle technologies and driving patterns.
Keywords: Environment and Environmental Studies

Under the Weather: Climate, Ecosystems, and Infectious Disease - National Research Council (The National Academies Press, 2001)
Since the dawn of medical science, people have recognized connections between a change in the weather and the appearance of epidemic disease. With today's technology, some hope that it will be possible to build models for predicting the emergence and spread of many infectious diseases based on climate and weather forecasts. However, separating the effects of climate from other effects presents a tremendous scientific challenge.
Keywords: Earth Sciences; Health and Medicine

Spurring Innovation in Food and Agriculture: A Review of the USDA Agriculture and Food Research Initiative Program - National Research Council (The National Academies Press, 2014)
The United States embarked on bold polices to enhance its food and agricultural system during the last half of the 19th century, investing first in the education of people and soon thereafter in research and discovery programs aimed at acquiring new knowledge needed to address the complex challenges of feeding a growing and hungry nation. Those policies, sustained over 125 years, have produced the most productive and efficient agricultural and food system in history. The U.S. Department of Agriculture (USDA) is the primary agency responsible for supporting innovations and advances in food and agriculture. USDA funds are allocated to support research through several mechanisms, including the Agriculture and Food Research Initiative (AFRI). In 2008, Congress replaced USDA's National Research Initiative with AFRI, creating USDA's flagship competitive research grants program, and the 2008 Food, Conservation, and Energy Act, known as the Farm Bill, outlined the structure of the new program. Spurring Innovation in Food and Agriculture assesses the effectiveness of AFRI in meeting the goals laid out by Congress and its success in advancing innovations and competitiveness in the U.S. food and agriculture system. Spurring Innovation in Food and Agriculture evaluates the value, relevance, quality, fairness, and flexibility of AFRI. This report also considers funding policies and mechanisms and identifies measures of the effectiveness and efficiency of AFRI's operation. The study examines AFRI's role in advancing science in relation to other research and grant programs inside of USDA as well as how complementary it is to other federal research and development programs. The findings and conclusions of this report will help AFRI improve its functions and effectiveness in meeting its goals and outcomes.
Keywords: Agriculture; Food and Nutrition

Adapting to the Impacts of Climate Change - National Research Council (The National Academies Press, 2010)
Across the United States, impacts of climate change are already evident. Heat waves have become more frequent and intense, cold extremes have become less frequent, and patterns of rainfall are likely changing. The proportion of precipitation that falls as rain rather than snow has increased across the western United States and Arctic sea ice has been reduced significantly. Sea level has been rising faster than at any time in recent history, threatening the natural and built environments on the coasts. Even if emissions of greenhouse gases were substantially reduced now, climate change and its resulting impacts would continue for some time to come. To date, decisions related to the management and protection of the nation's people, resources, and infrastructure have been based on records in the recent past, when climate was relatively stable. Adapting to the Impacts of Climate Change, part of the congressionally requested America's Climate Choices suite of studies, calls for a new paradigm-one that considers a range of possible future climate conditions and impacts that may be well outside the realm of past experience. Adaptation requires actions from many decision makers in federal, state, tribal, and local governments; the private sector; non-governmental organizations; and community groups. However, current efforts are hampered by a lack of solid information about the benefits, costs, and effectiveness of various adaptation options; climate information on regional and local scales; and a lack of coordination. Adapting to the Impacts of Climate Change calls for a national adaptation strategy that provides needed technical and scientific resources, incentives to begin adaptation planning, guidance across jurisdictions, shared lessons learned, and support of scientific research to expand knowledge of impacts and adaptation.
Keywords: Earth Sciences; Environment and Environmental Studies

Licensing Geographic Data and Services - National Research Council (The National Academies Press, 2004)
Geographic data are used in all sectors of society to support a huge range of applications ranging from emergency response to land-use planning to location-based services. In the past, government agencies typically acquired ownership of such data from private-sector and other data producers and distributed these data without restriction. Licensing--whereby the producer may restrict redistribution--has emerged as an alternative business model that agencies must now consider among a suite of procurement options. The report highlights licensing perspectives and experiences of major stakeholder groups and examines the pros and cons of licensing. It concludes that licensing may be a viable option in some instances and advises agencies on how to best serve societal interests.
Keywords: Earth Sciences

Exposure Science in the 21st Century: A Vision and a Strategy - National Research Council (The National Academies Press, 2012)
From the use of personal products to our consumption of food, water, and air, people are exposed to a wide array of agents each day—many with the potential to affect health. Exposure Science in the 21st Century: A Vision and A Strategy investigates the contact of humans or other organisms with those agents (that is, chemical, physical, and biologic stressors) and their fate in living systems. The concept of exposure science has been instrumental in helping us understand how stressors affect human and ecosystem health, and in efforts to prevent or reduce contact with harmful stressors. In this way exposure science has played an integral role in many areas of environmental health, and can help meet growing needs in environmental regulation, urban and ecosystem planning, and disaster management. Exposure Science in the 21st Century: A Vision and A Strategy explains that there are increasing demands for exposure science information, for example to meet needs for data on the thousands of chemicals introduced into the market each year, and to better understand the health effects of prolonged low-level exposure to stressors. Recent advances in tools and technologies—including sensor systems, analytic methods, molecular technologies, computational tools, and bioinformatics—have provided the potential for more accurate and comprehensive exposure science data than ever before. This report also provides a roadmap to take advantage of the technologic innovations and strategic collaborations to move exposure science into the future.
Keywords: Environment and Environmental Studies; Earth Sciences

Reducing Coastal Risk on the East and Gulf Coasts - National Research Council (The National Academies Press, 2014)
Hurricane- and coastal-storm-related losses have increased substantially during the past century, largely due to increases in population and development in the most susceptible coastal areas. Climate change poses additional threats to coastal communities from sea level rise and possible increases in strength of the largest hurricanes. Several large cities in the United States have extensive assets at risk to coastal storms, along with countless smaller cities and developed areas. The devastation from Superstorm Sandy has heightened the nation's awareness of these vulnerabilities. What can we do to better prepare for and respond to the increasing risks of loss? Reducing Coastal Risk on the East and Gulf Coasts reviews the coastal risk-reduction strategies and levels of protection that have been used along the United States East and Gulf Coasts to reduce the impacts of coastal flooding associated with storm surges. This report evaluates their effectiveness in terms of economic return, protection of life safety, and minimization of environmental effects. According to this report, the vast majority of the funding for coastal risk-related issues is provided only after a disaster occurs. This report calls for the development of a national vision for coastal risk management that includes a long-term view, regional solutions, and recognition of the full array of economic, social, environmental, and life-safety benefits that come from risk reduction efforts. To support this vision, Reducing Coastal Risk states that a national coastal risk assessment is needed to identify those areas with the greatest risks that are high priorities for risk reduction efforts. The report discusses the implications of expanding the extent and levels of coastal storm surge protection in terms of operation and maintenance costs and the availability of resources. Reducing Coastal Risk recommends that benefit-cost analysis, constrained by acceptable risk criteria and other important environmental and social factors, be used as a framework for evaluating national investments in coastal risk reduction. The recommendations of this report will assist engineers, planners and policy makers at national, regional, state, and local levels to move from a nation that is primarily reactive to coastal disasters to one that invests wisely in coastal risk reduction and builds resilience among coastal communities.
Keywords: Earth Sciences

Successful Response Starts with a Map: Improving Geospatial Support for Disaster Management - National Research Council (The National Academies Press, 2007)
In the past few years the United States has experienced a series of disasters, such as Hurricane Katrina in 2005, which have severely taxed and in many cases overwhelmed responding agencies. In all aspects of emergency management, geospatial data and tools have the potential to help save lives, limit damage, and reduce the costs of dealing with emergencies. Great strides have been made in the past four decades in the development of geospatial data and tools that describe locations of objects on the Earth's surface and make it possible for anyone with access to the Internet to witness the magnitude of a disaster. However, the effectiveness of any technology is as much about the human systems in which it is embedded as about the technology itself.
Keywords: Earth Sciences